Pengaruh Motivasi Belajar, Teknologi Digital Dan Fasilitas Perguruan Tinggi Dalam Meningkatkan Minat Belajar Mahasiswa Sekolah Tinggi Ilmu Manajemen Lembaga Pendidikan Indonesia Makassar - Hidayati, Andi (STIM-LPI Makassar, 2024)
The Influence of Learning Motivation, Digital Technology, and Campus Facilities in Increasing Student Interest in Study at STIM LPI Makassr This research aims to influence of learning motivation variables, digital technology, and campus facilities on the learning interest of students at the STIM LPI Makassar College of Management.. The research design used uses a quantitative research approach to examine an individual in a group using the multiple linear regression method with the help of SPSS 26. In this research, the population sampling technique uses the Slovin technique with a sample size of 100 people. The results of this research show that learning motivation does have a positive and not significant effect on interest in learning, whereas digital technology and facilities have a positive and significant effect on interest in learning. However, simultaneously learning motivation, technology and campus facilities have a positive and significant effect on students' interest in learning. students at the STIM LPI Makassar College of Management.